Pertumbuhan Jamur Merang (Volvariella volvaceae) pada Berbagai Media Tumbuh - MAYUN, IDA AYU (AGRITROP; Vol. 26, No. 3 September 2007)
The objective of this exsperiment was to study the effect of growth media on growth and yield of pady strawmushroom (Volvariella volvaceae). The semi laboratorium experiment was arranged in Randomized Complete Design or Fully Randomized Design (CRD) with six level treatment of growth media ie: a) paddy staw; b) fruit husk of the cofee; c) seagegrass; d) banana leaf; and e) woodsawdust. The data analysis in this experiment was: variance and LSD analysis, correlation analyisis, and analysis of regression. The results of this exsperiment was the treatment of media of woodsawdust cannot be used as a media growt of rank-mushroom because its failure to forming of fruitious body. Generaly can be said that the treatment of growth media of banana leaf as the best growth media of paddy straw-mushroom. Hereinafter, that a highest yield of fresh fruit body of pady straw-mushroom got from a treatment growth media of banana leaf that is as much 0.8785 kg m-2
Keywords: media tumbuh, badan buah, dan jamur merang (Volvariella volvaceae)